Concrete compressive strength variation due to cement source change. Issue 2 (8th April 2019) - Brown, Jared L.; Howard, Isaac L.; Varner, Robert
Abstract : Cementitious materials obtained from different sources, while evaluated and classified by the same methods and criteria, inevitably produce concrete with compressive strength variance despite other inputs and constituents remaining constant. This paper investigates the effect of cement by type and source on strength as a function of supplementary cementitious material (SCM) replacement and aggregate type. This was accomplished by compiling and analyzing compressive strength data from previous research initiatives and concluded that a cement source change can produce coefficient of variation, range, and range divided by average compressive strength values up to 18%, 2, 700 psi (18.6 MPa), and 0.40, respectively, at 14- to 56-day timeframes. Concrete that included SCMs displayed a statistically significant increase in compressive strength variation and a general decrease in compressive strength predictability versus mixtures without SCMs when a cement source was changed, and specific aggregate/cementitious material combinations influenced compressive strength variability due to a change in cement source.